PLANNING AND DEVELOPMENT OF A FAMILY ENTERTAINMENT CENTER WITH A PLAYFUL ARCHITECTURE APPROACH IN MEDAN: A MULTIDIMENSIONAL ARCHITECTURAL RESEARCH REPORT - Wahyu Abdillah; Luis Armando Simbolon (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This research report presents a comprehensive plan for the development of a family entertainment center designed through the lens of playful architecture in the city of Medan, North Sumatra. Titled “Funtastic Bound To Bond”, this project was conceived in response to the growing need for inclusive, safe, and educational recreational spaces amidst increasing urban density and the scarcity of adequate public open spaces in the Mebidang metropolitan area (Medan, Binjai Deli Serdang). By integrating three main conceptual pillars—Playful Connectivity with Local Memory, Intergenerational Bonding Space, and Experiential Multi-Level Recrea-Mall—this design aims to transform historical urban movement patterns into spatial explorations that foster intergenerational interaction. The theoretical foundation of this research is rooted in environmental psychology and family psychology, which specifically examine how behavioral settings and cognitive mapping can influence visitors’ moods and emotional well-being. The research methodology includes a systematic literature review, technical site analysis at Namo Simpur, user behavior observations, as well as international case studies such as LEGO House and Lotte World to ensure competitive quality standards. The design proposal suggests a layered recreational complex encompassing interactive play zones, thematic learning spaces, a public plaza, and an integrated commercial center supported by sustainable design strategies such as passive ventilation and natural lighting. This study concludes that a playful approach is not merely an aesthetic choice but a crucial architectural strategy for strengthening family bonds and urban identity in Medan.